2019
DOI: 10.1073/pnas.1812312116
|View full text |Cite
|
Sign up to set email alerts
|

Changing available energy for extratropical cyclones and associated convection in Northern Hemisphere summer

Abstract: The circulation of the Northern Hemisphere extratropical troposphere has changed over recent decades, with marked decreases in extratropical cyclone activity and eddy kinetic energy (EKE) in summer and increases in the fraction of precipitation that is convective in all seasons. Decreasing EKE in summer is partly explained by a weakening meridional temperature gradient, but changes in vertical temperature gradients and increasing moisture also affect the mean available potential energy (MAPE), which is the ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 47 publications
(60 reference statements)
0
28
0
Order By: Relevance
“…In addition to the stability changes discussed above, Gertler and O'Gorman [16] showed that the weakening of the surface meridional temperature gradient in mid-latitudes around NH land also contributes to the decrease of nonconvective MAPE (ΔMAPE ≈…”
Section: Decreased Surface Meridional Temperature Gradientmentioning
confidence: 95%
“…In addition to the stability changes discussed above, Gertler and O'Gorman [16] showed that the weakening of the surface meridional temperature gradient in mid-latitudes around NH land also contributes to the decrease of nonconvective MAPE (ΔMAPE ≈…”
Section: Decreased Surface Meridional Temperature Gradientmentioning
confidence: 95%
“…Storm track intensity defined using EKE is linearly related to MAPE in idealized simulations and reanalysis data (Gertler & O'Gorman, 2019;O'Gorman, 2010;O'Gorman & Schneider, 2008). In the simulations discussed in section 2.3, EKE is linearly related to MAPE, which we define following equation 3in O'Gorman and Schneider 2008:…”
Section: Mape Frameworkmentioning
confidence: 99%
“…Weakening of summertime westerlies and storm tracks is a robust feature supported by observations (Chang et al, 2016;Coumou et al, 2015), paleo-data (Routson et al, 2019), model simulations (Gertler and O'Gorman, 2019;Lehmann et al, 2014), physical understanding (Coumou et al, 2018;Hoskins and Woollings, 2015), and has been documented using multiple metrics (Chang et al, 2016;Coumou et al, 2015Coumou et al, , 2018Gertler and O'Gorman, 2019;Lehmann et al, 2014;O'Gorman, 2010;Petrie et al, 2015;Routson et al, 2019;Sussman et al, 2020). Since 2000, the Arctic has warmed at a rate at least twice as fast as the global average (Cohen et al, 2020;Coumou et al, 2015Coumou et al, , 2018.…”
Section: Introductionmentioning
confidence: 77%
“…Since 2000, the Arctic has warmed at a rate at least twice as fast as the global average (Cohen et al, 2020;Coumou et al, 2015Coumou et al, , 2018. This decreases the temperature gradient between the Arctic and (sub) tropics and weakens the mid-latitude westerlies and storm tracks (Chang et al, 2016;Coumou et al, 2015Coumou et al, , 2018Gertler and O'Gorman, 2019;Lehmann et al, 2014;O'Gorman, 2010;Petrie et al, 2015;Routson et al, 2019). These dynamical changes in boreal summer are also seen in climate models under greenhouse gas forcing (Chang et al, 2016;Coumou et al, 2018).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation